10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
This study examines the quality of life, stress, and coping strategies of parents raising children with autism spectrum disorder in Kathmandu Valley. These parents face unique challenges, including caregiving demands, societal stigma, and limited support resources. Limited research exists on the psychosocial impacts these parents experience in Nepal, making this study crucial for understanding their struggles. This cross-sectional mixed-method study was conducted in autism care centers across Kathmandu Valley. Quantitative data from 140 parents was collected using validated scales (Autism Parenting Stress Index, Brief-COPE, Multidimensional Scale of Perceived Social Support, and Family Quality of Life Scale), analyzed with STATA/EZR, while qualitative data from semi-structured interviews was thematically analyzed using R package for Qualitative Data Analysis. Purposive sampling ensured diverse experiences, and the tools were pretested for reliability and validity. Parents' greatest stressors were concerns about their child's future independence (76.43%), acceptance (72.14%), communication (66.43%), and social development (51.44%). They primarily relied on active coping and planning, with family providing more consistent support than friends. Unemployed parents had a lower family quality of life than homemakers (p = 0.003). Greater use of emotion-focused (p = 0.017) and problem-focused coping (p < 0.001) was associated with lower family quality of life. Parents mostly faced stress over their child's future and communication. They commonly used coping strategies like acceptance, emotional support, and religion, though some resorted to negative methods like self-blame, substance use and hitting the child. Challenges like societal stigma, limited support, financial strain, and disrupted family relationships were common. Parental support networks and perceived support significantly influenced family quality of life. This study highlights that these parents face various psychosocial burdens and struggles that affect their quality of life and they need interventions to reduce stigma, improve family well-being to ultimately improve their ability to care for their children.